Copyright in Periodicals during the Nineteenth Century: Balancing the Rights of Contributors and Publishers. - Cooper, Elena (Victorian Periodicals Review, 2018)
This article provides an overview of nineteenth-century copyright rules balancing the rights of contributors and publishers in periodical works as enacted in section 18 of the 1842 Literary Copyright Act and as further debated in the later nineteenth century. With a view to instigating a conversation between law and the humanities, this study highlights perceptions of the social importance of different genres—encyclopedias, reviews, magazines, and periodical works—as expressed in nineteenth-century copyright debates.